Implementasi Sasaran Keselamatan Pasien Berdasarkan Standar Komisi Akreditasi Rumah Sakit (KARS) Di RSUD Wonosari Yogyakarta: Implementation of Patient Safety Indicators Based on Hospital Accreditation Commisions (KARS) Standars at Public Hospital Wonosari, Yogyakarta - Wahid, Najwiah A.; Mudayana, Ahmad Ahid (International Journal of Healthcare Research, 2022)
Background:  The safety of patient was important component in quality of service in health. The hospital of Wonosari was belongs to the government districts of Gunung Kidul type C whom has contribution in services of health for people. In 2016 facilities like barcode not yet in all rooms, human resources have not consistenly reported KTD, the bathroom floor was slippery so that it can cause an incidence of patient safety risk. Now overall the implementation of patient safety has been running optimally, such as the availability of supporting facilities and later of SOP, socoalization and training on evaluation and supervision have been held. The aims of this study to analyze the implementation of patient safety goals based on the hospital accreditation standards (KARS) at RSUD Wonosari Yogyakarta. Methods: this studied used qualitative methods through in-depth interviews, observation and document review. Data collection was done by interviewing 5 informants Results: Identification of patients using two identities, effective communication with SBAR and TBaK, stores medications that need to be watched out in a separate place, tagging used checklist patient at surgery, applied 6 steps and 5 handwashing moments from WHO, conduct initial assessment and reassessment of patients at risk of falled. Conclusion: The implementation of patient safety goals based on the KARS standard in RSUD Wonosari Yogyakarta has been running optimally.